Faktor Ekonomi Memengaruhi Pernikahan Remaja Perempuan - Fitriyani, Dian (Jurnal Kebidanan Malakbi, 2021)
World Health Organization (WHO) in collaboration with UNICEF which aims to improve the health of mothers and newborns in 25 countries that contributed the highest maternal mortality rate, one of them is in Indonesia. Adolescent who become pregnant will increase the health risks for her and baby. The maternal mortality reach approximately 70,000 deaths each year and maternal mortality is closely related to pregnancy and childbirth by adolescents aged 15 – 19 years in the worldwide. Objective of the research is to analyze the factors that influence adolescent girls’ marriage in Indramayu regency. This study uses qualitative method, the paradigm fenomenology. The subjects taken by purposive sampling technique. The informants is adolescent women who married about aged <20 years, her husband, and her family as much as 21 people. The results shows that family economic factors affecting marriage adolescent girls in the Indramayu regency that is caused economic status, the attitude of materialistic. Limitations of the study, there are several girls who live outside the city because they took the husband or for work outside the city, so it's likely there are many factors that have not been revealed. Economic factors affecting marriage adolescent girls in Indramayu regency, is causes by economic status and the attitude of materialistic. It is necessary to consider the policy of the Marriage Law with the age of >20 years and the prohibition of marriages <20 years so that young girls avoid negative impacts, both physical and psychological.